Antioxidant and anti-proliferative potential of Cardiospermum halicacabum stem extracts against human breast cancer (MCF-7) cells - Krithika, N.; Chittibabu, C. V.; Santhanapandi, P.; Lenin, M. (Current Botany, 2022)
Cancer is the most important health care problem worldwide. An estimated 10 million new cases worldwide are recorded annually, of which 46% are in developed countries. Breast cancer is one of the second most common malignant tumors in the world. All forms of cancer treatment, including surgical treatment, chemotherapy and/or radiotherapy are often poor and often toxic to the normal cell. Therefore, there is still an urgent need for new cancer treatment options. More research is now being done to determine which compounds occur naturally. The current study aims to extract Cardiospermum halicacabum L. for the prevention and treatment of cancer. A few methods may account for the perceived therapeutic effects, most importantly direct cytotoxicity. These herbal medicines when combined with regular antioxidant and anticancer drugs may be helpful in combining the antioxidant and anticancer effects and reducing the side effects associated with common drugs.